Infection, reinfection, and postvaccination incidence of SARS-CoV-2 and associated risks in healthcare workers in Tamil Nadu: A retrospective cohort study - Boopathy Nisha; Keerthana Dakshinamoorthy; Preeti Padmanaban; Timsi Jain; Manju Neelavarnan (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The study was conducted in response to the need to understand the incidence of SARS-CoV2 infection and its determinants in healthcare workers (HCWs) and describe the epidemiology and presentation of reinfection cases. Also, we intended to determine the incidence of post-vaccination infections among health care workers as well as the contributing factors. MATERIALS AND METHODS: Retrospective cohort design was used to quantify the coronavirus disease (COVID-19) infection among HCWs. The study cohort was all healthcare personnel working during the month of June 2021 in a tertiary care medical college hospital. Individuals diagnosed with laboratory-confirmed positive real-time polymerase chain reaction tests for SARS-CoV-2 infection between March 20, 2020, and May 31, 2021, were included. Univariate and multivariate analysis with Cox regression model elicited potential risk factors for all infections in HCWs. RESULTS: A total of 2420 HCWs constituted the cohort, in which the majority were primary healthcare providers (67.1%) and others. The mean age of the cohort was 30.27 years ± 10.53 standard deviation. The cumulative incidence of infection, reinfection, and postvaccination infection was 144.6 cases, 11.4 individuals, and 66.5 per 1000 HCWs respectively. Chronic illness was significantly associated with all infections. However, males and primary-care providers had higher risk of infection, whereas among the postvaccinated participants, partial vaccination status was one of the determinants. CONCLUSION: Based on the findings, we endorse stringent testing and encourage HCWs to mandatorily follow COVID-appropriate behavior even if they are completely vaccinated and after recovery from previous infection